Age-Related Vestibular Loss: Current Understanding and Future Research Directions - Allen, Dominic; Ribeiro, Luis; Arshad, Qadeer; Seemungal, Barry M. (Frontiers in Neurology, 2017)
The vestibular system subserves a number of reflex and perceptual functions, comprising the peripheral apparatus, the vestibular nerve, the brainstem and cerebellar processing circuits, the thalamic relays and the vestibular cerebral cortical network. This system provides signals of self-motion, important for gaze and postural control, and signals of travelled distance, for spatial orientation, especially in the dark. Current evidence suggests that certain aspects of this multi-faceted system, may deteriorate with age, sometimes with severe consequences, such as falls. Often the deterioration in vestibular functioning relates to how the signal is processed by brain circuits rather than an impairment in the sensory transduction process. We review current data concerning age-related changes in the vestibular system, and how this may be important for clinicians dealing with balance disorders.